2020
DOI: 10.24198/mfarmasetika.v4i0.25877
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Penghambatan Polimerisasi Hem Ekstrak Etanol Daun Cambai Utan (Piper porphyrophyllum)

Abstract: Resistensi Plasmodium terhadap obat malaria mengakibatkan kegagalan pengobatan. Oleh karena itu ketersediaan antimalaria baru sangat diperlukan untuk melawan resistensi. Pencarian obat baru terus dilakukan melalui berbagai cara termasuk eksplorasi tanaman yang berpotensi sebagai antimalaria. Penelitian ini bertujun untuk menentukan aktivitas penghambatan polimerissi hem dari ekstrak etanol daun Cambai Utan (Piper porphyrophyllum) berdasarkan nilai IC50. Pengujian aktivitas penghambatan polimerisasi hem merupak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Even if a great number of research has shown low AuNP cytotoxicity [210], the wide available literature includes contradictory data because of the diverse cell lines, cell viability assays, the chemical routes employed for AuNP synthesis [211], and the absence of standard safety protocols. Several research studies have been conducted focusing on the relationship between the AuNP properties and cell death mechanisms for different types of tumor cells, and the cellular mechanisms studied are apoptosis, necrosis, and autophagy [212]. It was shown that smaller AuNPs tended to induce more necrosis, and hexagonal ones and nanorods causes more apoptosis, while AuNPs with hydrophobic functions induced greater apoptosis and autophagy than hydrophilic ones.…”
Section: Biodistribution and Cytotoxicity Of Aunpmentioning
confidence: 99%
“…Even if a great number of research has shown low AuNP cytotoxicity [210], the wide available literature includes contradictory data because of the diverse cell lines, cell viability assays, the chemical routes employed for AuNP synthesis [211], and the absence of standard safety protocols. Several research studies have been conducted focusing on the relationship between the AuNP properties and cell death mechanisms for different types of tumor cells, and the cellular mechanisms studied are apoptosis, necrosis, and autophagy [212]. It was shown that smaller AuNPs tended to induce more necrosis, and hexagonal ones and nanorods causes more apoptosis, while AuNPs with hydrophobic functions induced greater apoptosis and autophagy than hydrophilic ones.…”
Section: Biodistribution and Cytotoxicity Of Aunpmentioning
confidence: 99%
“…31,32 Studies of PC3 cells have also shown decreased internalization of particles in the presence of serum. 6 When our group recently compared the interaction of gold nanoparticles of different morphologies (spheres, cubes, prisms, and rods) yet coated with the same surfactant (CTAB) with the human serum, we noted that the strength of serum−nanoparticle interactions is remarkably influenced by the particle morphol-ogy. 33 Another study from our group on Ag nanoparticles of similar shape and size yet of different capping agents has revealed that the surface ligands also greatly influence the nanoparticle−serum interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Variation of nanoscale gold geometry has been shown to affect its optical properties, the available surface area, and transport properties. 18 Gold nanostructures display self-therapeutic properties to fight cancers, including inhibition of tumoral angiogenesis, 19,20 inhibition of mitogen-activated protein kinase (MAPK) signaling to reverse epithelial-mesenchymal transition in cancer, 21 and alteration of nonviral gene delivery uptake pathways to avoid lysosomal degradation. 22 Alternatively, nanoscale gold is readily modified by electrostatic interactions or gold−thiol (Au−S) bonds, allowing facile functionalization with a variety of therapeutics, polymers, and targeting ligands.…”
Section: Inorganic Building Blocksmentioning
confidence: 99%